Steel material used as material for fastening member, and fastening member
By controlling the chemical composition and element content of steel to satisfy the characteristic formula (Formula 1), the corrosion resistance and hydrogen embrittlement resistance of steel are significantly improved in corrosive environments containing chloride ions, thus solving the problems of paint peeling and accelerated corrosion in bridges and buildings in coastal areas.
Patent Information
- Application Number
- CN202280096155.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2022-05-17
- Publication Date
- 2025-01-07
AI Technical Summary
Existing technologies struggle to simultaneously improve the corrosion resistance and hydrogen embrittlement resistance of steel in corrosive environments containing chloride ions, especially in bridges and buildings in coastal areas where coatings are prone to peeling and corrosion is exacerbated.
By controlling the chemical composition and element content of steel to meet specific chemical composition ranges, and by adjusting the synergistic effect between elements through characteristic formula (Formula 1), the pH of the steel surface can be suppressed, hydrogen generation and intrusion can be reduced, and corrosion resistance and hydrogen embrittlement resistance can be improved.
In corrosive environments containing chloride ions, it significantly improves the corrosion resistance and hydrogen embrittlement resistance of steel, ensuring long-term reliability for use in bridges and buildings in coastal areas.
Smart Images

Figure CN119278286A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a steel material and a fastening member, and more particularly to a steel material used as a material of a fastening member such as a bolt, a nut, or a washer, and a fastening member formed of the steel material. Background Art
[0002] Fastening members such as bolts, nuts or washers are used for fastening industrial machinery, automobiles, bridges and buildings. Among these uses, bridges, buildings, etc. are sometimes built in coastal areas. The coastal areas are corrosive environments with many chloride ions. Therefore, even if the above-mentioned fastening members are coated, the coating may sometimes peel off and corrosion may intensify. Therefore, for the fastening members used in the above-mentioned corrosive environment containing chloride ions, excellent corrosion resistance is required.
[0003] Furthermore, hydrogen embrittlement is likely to occur in a corrosive environment containing chloride ions. Therefore, a fastening member used in a corrosive environment containing chloride ions is required to have not only excellent corrosion resistance but also excellent hydrogen embrittlement resistance.
[0004] Japanese Patent Application Laid-Open No. 2020-180325 (Patent Document 1) and Japanese Patent Application Laid-Open No. 2017-226878 (Patent Document 2) propose technologies related to improving corrosion resistance.
[0005] The steel material disclosed in Patent Document 1 has the following composition, which contains, by mass%, C: 0.15% to 0.25%, Si: 0.05% to 0.30%, Mn: 0.50% to 1.80%, P: 0.002% to 0.030%, S: 0.0005% to 0.0200%, Al: 0.010% to 0.065%, Cu: 0.01% to 0.48%, Nb: 0.005% to 0.030%, Sn: 0.005% to 0.200%, Ti: 0.005% to 0.200%, B: 0.0001% to 0.0050%, N: 0.0020% to 0.0100%, and O: 0.0025%, with the remainder being iron and unavoidable impurities. The document states that the corrosion resistance of the steel in a corrosive environment is improved by containing Cu, Nb and Sn.
[0006] The steel material disclosed in Patent Document 2 has the following composition, which contains, by mass%, C: 0.15% or more and less than 0.30%, Si: 0.05% or more and less than 1.00%, Mn: 0.20% or more and less than 2.00%, P: 0.001% or more and less than 0.030%, S: 0.0001% or more and less than 0.0100%, Al: 0.010% or more and less than 0.100%, Cu: 0.010% or more and less than 1.000%, Nb: 0.005% or more and less than 0.200%, Sn: 0.005% or more and less than 0.200%, and N: 0.0010% or more and less than 0.0100%, and the balance is iron and unavoidable impurities. The document states that by containing Cu, Nb, Sn and Ni, the corrosion resistance of the steel material in a corrosive environment is improved.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: Japanese Patent Application Publication No. 2020-180325
[0010] Patent Document 2: Japanese Patent Application Publication No. 2017-226878 Summary of the invention
[0011] Problems to be solved by the invention
[0012] However, the corrosion resistance and hydrogen embrittlement resistance may be improved in a manner different from that of the steel materials disclosed in Patent Documents 1 and 2.
[0013] An object of the present disclosure is to provide a steel material and a fastening member having excellent corrosion resistance and excellent hydrogen embrittlement resistance.
[0014] Methods used to solve problems
[0015] The steel material of the present disclosure has the following configuration.
[0016] A steel material comprising, by mass %,
[0017] C: 0.15~0.45%,
[0018] Si: 0.01-1.00%,
[0019] Mn: 0.01~1.50%,
[0020] P: 0.050% or less,
[0021] S: 0.050% or less,
[0022] Al: 0.100% or less,
[0023] Sn: 0.02~0.30%,
[0024] Cr: 0.20% or less,
[0025] Cu: 0.010~0.500%,
[0026] Ni: 0.01~0.50%,
[0027] Mo: 0.01~0.50%,
[0028] Ti: 0.001~0.100%,
[0029] One or more selected from Co, Sb, Ge and In: 0.0013% or more and less than 0.0065% in total,
[0030] N: 0.010% or less,
[0031] O: 0.015% or less,
[0032] W: 0~0.50%,
[0033] B: 0~0.0050%,
[0034] Nb: 0~0.300%,
[0035] Ca: 0~0.0050%,
[0036] Mg: 0~0.0050%,
[0037] Rare earth elements: 0 to 0.0200%, and
[0038] Balance: Fe and impurities,
[0039] The steel material satisfies formula (1):
[0040] 23<10×LN(Cu+0.5×Sn+2000×Tx)+100×(0.5×Ni+Mo) 3 -100×(0.5×Ni+Mo) 2 +30×(0.5×Ni+Mo)+10<39 (1)
[0041] In the formula, the element symbol in formula (1) is substituted by the content of the corresponding element in mass %, Tx is substituted by the total content of one or more selected from Co, Sb, Ge and In in mass %, and LN in formula (1) refers to the natural logarithm.
[0042] The fastening member of the present disclosure is composed of the above-mentioned steel material.
[0043] Effects of the Invention
[0044] The steel material and the fastening member disclosed in the present invention have excellent corrosion resistance and excellent hydrogen embrittlement resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 This is an example of a photographic image of the microstructure of the steel material according to the present embodiment.
[0046] Figure 2 This is a schematic diagram showing an example of a graph showing the relationship between the amount of hydrogen intrusion and the fracture load obtained by a SSRT test under hydrogen charging. DETAILED DESCRIPTION
[0047] The present inventors investigated and studied steel materials having excellent corrosion resistance and excellent hydrogen embrittlement resistance. As a result, they obtained the following findings.
[0048] In order to improve the corrosion resistance and hydrogen embrittlement resistance of steel, it is effective to reduce the Cr content in the steel as much as possible. In addition, Cu, Ni and Sn can significantly improve the corrosion resistance of steel. Based on the discussion from the above chemical composition point of view, the inventors of the present invention have discussed the chemical composition of steel with excellent corrosion resistance and excellent hydrogen embrittlement resistance. As a result, the inventors of the present invention believe that if the steel has the following chemical composition, its corrosion resistance and hydrogen embrittlement resistance are improved even in a corrosive environment containing chloride ions. The chemical composition contains, in mass%, C: 0.15-0.45%, Si: 0.01-1.00%, Mn: 0.01-1.50%, P: less than 0.050%, S: less than 0.050%, Al: less than 0.100%, Sn: 0.02-0.30%, Cr: 0.20% or more. Below, Cu: 0.010~0.500%, Ni: 0.01~0.50%, Mo: 0.01~0.50%, Ti: 0.001~0.100%, N: less than 0.010%, O: less than 0.015%, W: 0~0.50%, B: 0~0.0050%, Nb: 0~0.300%, Ca: 0~0.0050%, Mg: 0~0.0050%, rare earth elements: 0~0.0200%, and the balance: Fe and impurities.
[0049] However, even steel materials having the above chemical composition may not obtain sufficient corrosion resistance and sufficient hydrogen embrittlement resistance in a corrosive environment containing chloride ions. Therefore, the present inventors have investigated and studied the reasons for the reduction of corrosion resistance and hydrogen embrittlement resistance of the steel materials having the above chemical composition. As a result, the present inventors believe that in a corrosive environment containing chloride ions, corrosion is aggravated by the following mechanism.
[0050] When fastening members such as bolts, nuts or washers are used in buildings such as bridges in coastal areas, as described above, chloride ions will be scattered to the surface of the steel material constituting the fastening members. In addition, due to fog, rainfall, etc., water containing the scattered chloride ions will adhere to the surface of the steel material. As a result, the surface of the steel material becomes wet (wetting process), and then becomes a state where the water containing chloride ions is dried from the surface of the steel material (drying process).
[0051] In such an environment, especially during the drying process, the dissolution of Fe on the steel surface is promoted. The dissolved Fe makes the steel surface an acidic environment. That is, as the dissolution of Fe proceeds, the pH at the steel surface decreases. The lower the pH, the further the dissolution of Fe proceeds. That is, corrosion will intensify.
[0052] Based on the above research results, the present inventors believed that as long as the decrease in pH on the surface of the steel material can be suppressed, the dissolution of Fe can be suppressed. Therefore, elements that can suppress the decrease in pH in the acidic region of pH 0 to 7 were studied. The present inventors found that, as a result, if any one or more of Co, Sb, Ge and In is contained in addition to the above-mentioned Cu, Ni and Sn, the decrease in pH can be suppressed in a wide range in the acidic region, and as a result, the dissolution of Fe can be suppressed in the drying process.
[0053] Based on the above research results, the inventors further studied the chemical composition of the steel. As a result, the inventors found that if the above chemical composition further contains one or more selected from Co, Sb, Ge and In in a total range of 0.0013% or more and less than 0.0065%, the corrosion resistance and hydrogen embrittlement resistance in a corrosive environment containing chloride ions are further improved. In other words, the inventors found that by making the steel satisfy the following feature 1, the corrosion resistance and hydrogen embrittlement resistance in a corrosive environment containing chloride ions are further improved.
[0054] (Feature 1)
[0055] The chemical composition includes, by mass%, C: 0.15-0.45%, Si: 0.01-1.00%, Mn: 0.01-1.50%, P: 0.050% or less, S: 0.050% or less, Al: 0.100% or less, Sn: 0.02-0.30%, Cr: 0.20% or less, Cu: 0.010-0.500%, Ni: 0.01-0.50%, Mo: 0.01-0.50%, Ti: 0.0 01~0.100%, one or more selected from Co, Sb, Ge and In: a total of 0.0013% or more and less than 0.0065%, N: less than 0.010%, O: less than 0.015%, W: 0~0.50%, B: 0~0.0050%, Nb: 0~0.300%, Ca: 0~0.0050%, Mg: 0~0.0050%, rare earth elements: 0~0.0200%, and the balance: Fe and impurities.
[0056] However, for the steel material having the above chemical composition, it is not possible to fully take into account both excellent corrosion resistance and excellent hydrogen embrittlement resistance in a corrosive environment containing chloride ions. Therefore, for the steel material having the above chemical composition, the present inventors have further studied the method of obtaining excellent corrosion resistance and excellent hydrogen embrittlement resistance.
[0057] As a result of the studies, the present inventors have found that excellent corrosion resistance and excellent hydrogen embrittlement resistance can be obtained by further satisfying the following characteristic 2 in a steel material satisfying the above-mentioned characteristic 1.
[0058] (Feature 2)
[0059] The chemical composition of the steel further satisfies the formula (1).
[0060] 23<10×LN(Cu+0.5×Sn+2000×Tx)+100×(0.5×Ni+Mo) 3 -100×(0.5×Ni+Mo) 2 +30×(0.5×Ni+Mo)+10<39 (1)
[0061] Here, the content of the corresponding element in mass % is substituted for the element symbol in formula (1), and the total content of one or more selected from Co, Sb, Ge and In in mass % is substituted for Tx. LN in formula (1) means natural logarithm.
[0062] Definition: F1 = 10 × LN (Cu + 0.5 × Sn + 2000 × Tx) + 100 × (0.5 × Ni + Mo) 3 -100×(0.5×Ni+Mo) 2+30×(0.5×Ni+Mo)+10. Among the elements in the chemical composition that satisfies feature 1, Cu, Sn, Co, Sb, Ge, and In improve corrosion resistance in an environment containing chloride ions, and also inhibit the generation of hydrogen caused by the reduction reaction based on corrosion. If the generation of hydrogen can be suppressed, the amount of hydrogen in contact with the surface of the steel will decrease. Therefore, the amount of hydrogen that penetrates into the steel from the surface of the steel will also decrease. As a result, hydrogen embrittlement resistance is improved. Therefore, Cu, Sn, Co, Sb, Ge, and In are an element group that improves corrosion resistance and inhibits the generation of hydrogen to improve hydrogen embrittlement resistance.
[0063] On the other hand, among the elements in the chemical composition satisfying Feature 1, Ni and Mo improve or reduce corrosion resistance and hydrogen embrittlement resistance according to their contents through the synergistic effect with Sn in the chemical composition of Feature 1. Specifically, in the chemical composition satisfying Feature 1, although the corrosion resistance and hydrogen embrittlement resistance are improved when the content of Ni and Mo is within a certain range, the corrosion resistance and hydrogen embrittlement resistance will decrease in different ranges. It can be considered that the level of corrosion resistance and hydrogen embrittlement resistance based on Ni and Mo is affected by the synergistic effect of Ni and Mo with Sn. The "100×(0.5×Ni+Mo)" in F1 3 -100×(0.5×Ni+Mo) 2 +30×(0.5×Ni+Mo)+10” is a cubic formula. This cubic formula represents the relationship between the Ni and Mo contents and the corrosion resistance and hydrogen embrittlement resistance in the chemical composition of feature 1 containing Sn.
[0064] When F1 is higher than 23 and lower than 39, the relationship between the contents of Cu, Sn, Co, Sb, Ge and In and the contents of Ni and Mo is appropriate in the chemical composition satisfying feature 1. Therefore, in a corrosive environment containing chloride ions, both excellent corrosion resistance and excellent hydrogen embrittlement resistance can be achieved.
[0065] The steel material of the present embodiment completed based on the above findings has the following configuration. [1]
[0067] A steel material, which consists of the following components in mass %:
[0068] C: 0.15~0.45%,
[0069] Si: 0.01-1.00%,
[0070] Mn: 0.01~1.50%,
[0071] P: 0.050% or less,
[0072] S: 0.050% or less,
[0073] Al: 0.100% or less,
[0074] Sn: 0.02~0.30%,
[0075] Cr: 0.20% or less,
[0076] Cu: 0.010~0.500%,
[0077] Ni: 0.01~0.50%,
[0078] Mo: 0.01~0.50%,
[0079] Ti: 0.001~0.100%,
[0080] One or more selected from Co, Sb, Ge and In: 0.0013% or more and less than 0.0065% in total,
[0081] N: 0.010% or less,
[0082] O: 0.015% or less,
[0083] W: 0~0.50%,
[0084] B: 0~0.0050%,
[0085] Nb: 0~0.300%,
[0086] Ca: 0~0.0050%,
[0087] Mg: 0~0.0050%,
[0088] Rare earth elements: 0 to 0.0200%, and
[0089] Balance: Fe and impurities,
[0090] The steel material satisfies formula (1):
[0091] 23<10×LN(Cu+0.5×Sn+2000×Tx)+100×(0.5×Ni+Mo) 3 -100×(0.5×Ni+Mo) 2 +30×(0.5×Ni+Mo)+10<39 (1)
[0092] In the formula, the content of the corresponding element in mass % is substituted in the element symbol in formula (1), the total content of one or more selected from Co, Sb, Ge and In in mass % is substituted in Tx, and LN in formula (1) refers to the natural logarithm. [2]
[0094] The steel material according to [1], comprising one or more selected from the following:
[0095] W: 0.01~0.50%,
[0096] B: 0.0001~0.0050%,
[0097] Nb: 0.001~0.300%,
[0098] Ca: 0.0001~0.0050%,
[0099] Mg: 0.0001 to 0.0050%, and
[0100] Rare earth elements: 0.0001~0.0200%. [3]
[0102] A fastening member, comprising the steel material described in [1] or [2].
[0103] Hereinafter, the steel material and the fastening member of the present embodiment will be described in detail. It should be noted that "%" related to an element means mass % unless otherwise specified.
[0104] [Features of the Steel Material of the Present Embodiment]
[0105] The steel material of this embodiment satisfies the following characteristics 1 and 2.
[0106] (Feature 1)
[0107] The chemical composition includes, by mass%, C: 0.15-0.45%, Si: 0.01-1.00%, Mn: 0.01-1.50%, P: 0.050% or less, S: 0.050% or less, Al: 0.100% or less, Sn: 0.02-0.30%, Cr: 0.20% or less, Cu: 0.010-0.500%, Ni: 0.01-0.50%, Mo: 0.01-0.50%, Ti: 0.0 01~0.100%, one or more selected from Co, Sb, Ge and In: a total of 0.0013% or more and less than 0.0065%, N: less than 0.010%, O: less than 0.015%, W: 0~0.50%, B: 0~0.0050%, Nb: 0~0.300%, Ca: 0~0.0050%, Mg: 0~0.0050%, rare earth elements: 0~0.0200%, and the balance: Fe and impurities.
[0108] (Feature 2)
[0109] The chemical composition of the steel further satisfies the formula (1).
[0110] 23<10×LN(Cu+0.5×Sn+2000×Tx)+100×(0.5×Ni+Mo) 3 -100×(0.5×Ni+Mo) 2 +30×(0.5×Ni+Mo)+10<39 (1)
[0111] Here, the element symbol in formula (1) is replaced by the content of the corresponding element in mass %, and Tx is replaced by the total content of one or more selected from Co, Sb, Ge and In in mass %. LN in formula (1) means natural logarithm.
[0112] Hereinafter, feature 1 and feature 2 will be described.
[0113] [Regarding (Feature 1) Content of each element in the chemical composition]
[0114] The chemical composition of the steel material of the present embodiment contains the following elements.
[0115] C: 0.15~0.45%
[0116] Carbon (C) improves the hardenability of steel and increases the strength of the fastening member made of the steel. If the C content is less than 0.15%, the above effects cannot be fully obtained even if the contents of other elements are within the range of the present embodiment.
[0117] On the other hand, if the C content exceeds 0.45%, the cold forgeability of the steel material decreases even if the contents of other elements are within the ranges of the present embodiment.
[0118] Therefore, the C content is 0.15 to 0.45%.
[0119] The lower limit of the C content is preferably 0.18%, more preferably 0.20%, and further preferably 0.22%.
[0120] The upper limit of the C content is preferably 0.43%, more preferably 0.41%, and further preferably 0.39%.
[0121] Si: 0.01~1.00%
[0122] Silicon (Si) improves the strength of the fastening member made of steel by solid solution strengthening. If the Si content is less than 0.01%, the above effects cannot be fully obtained even if the contents of other elements are within the range of the present embodiment.
[0123] On the other hand, if the Si content exceeds 1.00%, the cold forgeability of the steel material decreases even if the contents of other elements are within the ranges of the present embodiment.
[0124] Therefore, the Si content is 0.01 to 1.00%.
[0125] The lower limit of the Si content is preferably 0.02%, more preferably 0.03%, and further preferably 0.05%.
[0126] The upper limit of the Si content is preferably 0.90%, more preferably 0.80%, more preferably 0.70%, more preferably 0.60%, and still more preferably 0.50%.
[0127] Mn: 0.01~1.50%
[0128] Manganese (Mn) improves the hardenability of steel and increases the strength of the fastening member made of the steel. If the Mn content is less than 0.01%, the above effects cannot be fully obtained even if the contents of other elements are within the range of the present embodiment.
[0129] On the other hand, if the Mn content exceeds 1.50%, the cold forgeability of the steel material decreases even if the contents of other elements are within the ranges of the present embodiment.
[0130] Therefore, the Mn content is 0.01 to 1.50%.
[0131] The lower limit of the Mn content is preferably 0.05%, more preferably 0.10%, and further preferably 0.15%.
[0132] The upper limit of the Mn content is preferably 1.40%, more preferably 1.30%, and further preferably 1.20%.
[0133] P: 0.050% or less
[0134] Phosphorus (P) is an impurity. That is, the lower limit of the P content is greater than 0%.
[0135] If the P content exceeds 0.050%, P will segregate at the grain boundaries even if the contents of other elements are within the ranges of the present embodiment. As a result, the hydrogen embrittlement resistance of the steel material will decrease.
[0136] Therefore, the P content is set to 0.050% or less.
[0137] It is preferred that the P content be as low as possible. However, an extreme reduction in the P content will significantly increase the manufacturing cost. Therefore, in consideration of industrial production, the preferred lower limit of the P content is 0.001%, more preferably 0.002%, and even more preferably 0.003%.
[0138] The upper limit of the P content is preferably 0.040%, more preferably 0.030%, and further preferably 0.020%.
[0139] S: 0.050% or less
[0140] Sulfur (S) is an impurity. That is, the lower limit of the S content is greater than 0%.
[0141] If the S content exceeds 0.050%, S will segregate at the grain boundaries even if the contents of other elements are within the ranges of the present embodiment. As a result, the hydrogen embrittlement resistance of the steel material will decrease.
[0142] Therefore, the S content is set to 0.050% or less.
[0143] The S content is preferably as low as possible. However, an extreme reduction in the S content will significantly increase the manufacturing cost. Therefore, in consideration of industrial production, the preferred lower limit of the S content is 0.001%, more preferably 0.002%, and even more preferably 0.003%.
[0144] The upper limit of the S content is preferably 0.040%, more preferably 0.030%, and further preferably 0.020%.
[0145] Al: 0.100% or less
[0146] Aluminum (Al) is inevitably contained. That is, the Al content is greater than 0%.
[0147] Al deoxidizes the steel. If Al is contained, even if the content is small, the above-mentioned effect can be obtained to a certain extent.
[0148] However, if the Al content exceeds 0.100%, even if the contents of other elements are within the range of the present embodiment, coarse Al nitrides will be generated. Coarse Al nitrides will become the starting point of fracture, thereby reducing the workability of the steel material.
[0149] Therefore, the Al content is set to 0.100% or less.
[0150] The lower limit of the Al content is preferably 0.001%, more preferably 0.010%, and further preferably 0.015%.
[0151] The upper limit of the Al content is preferably 0.090%, more preferably 0.080%, and further preferably 0.070%.
[0152] In the chemical composition of the steel material of the present embodiment, the Al content refers to the total Al (Total-Al) content.
[0153] Sn: 0.02~0.30%
[0154] Tin (Sn) improves the corrosion resistance and hydrogen embrittlement resistance of steel materials in corrosive environments. If the Sn content is less than 0.02%, the above effects cannot be fully obtained even if the contents of other elements are within the ranges of the present embodiment.
[0155] On the other hand, if the Sn content exceeds 0.30%, Sn will segregate at the grain boundaries even if the contents of other elements are within the ranges of the present embodiment. In this case, the hot workability of the steel material decreases.
[0156] Therefore, the Sn content is 0.02 to 0.30%.
[0157] The lower limit of the Sn content is preferably 0.03%, more preferably 0.05%, and further preferably 0.10%.
[0158] The upper limit of the Sn content is preferably 0.25%, more preferably 0.20%, further preferably 0.15%, further preferably 0.10%.
[0159] Cr: 0.20% or less
[0160] In the steel of this embodiment, the Cr content exceeds 0%. Cr improves the hardenability of the steel. Cr reduces the corrosion resistance and hydrogen embrittlement resistance of the steel in a corrosive environment. If the Cr content exceeds 0.20%, the corrosion resistance and hydrogen embrittlement resistance of the steel will be reduced even if the contents of other elements are within the range of this embodiment.
[0161] Therefore, the Cr content is set to 0.20% or less.
[0162] The Cr content is preferably as low as possible. However, an extreme reduction in the Cr content will significantly increase the manufacturing cost. Therefore, in consideration of industrial production, the preferred lower limit of the Cr content is 0.01%, more preferably 0.02%, and even more preferably 0.03%.
[0163] The upper limit of the Cr content is preferably 0.15%, more preferably 0.10%, and even more preferably 0.07%. The upper limit of the Cr content which is more effective for further improving the corrosion resistance and hydrogen embrittlement resistance of the steel material is preferably less than 0.05%.
[0164] Cu: 0.010~0.500%
[0165] Copper (Cu) improves the corrosion resistance and hydrogen embrittlement resistance of steel materials in corrosive environments. If the Cu content is less than 0.010%, the above effects cannot be fully obtained even if the contents of other elements are within the ranges of the present embodiment.
[0166] On the other hand, if the Cu content exceeds 0.500%, the steel material is prone to red-hot embrittlement, and the corrosion resistance and hydrogen embrittlement resistance of the steel material are reduced.
[0167] Therefore, the Cu content is 0.010 to 0.500%.
[0168] The lower limit of the Cu content is preferably 0.050%, more preferably 0.100%, more preferably 0.150%, more preferably 0.200%, and still more preferably 0.250%.
[0169] The upper limit of the Cu content is preferably 0.450%, more preferably 0.400%.
[0170] Ni: 0.01~0.50%
[0171] Nickel (Ni) improves the hardenability of steel and the strength of fasteners made of steel. Ni further improves the corrosion resistance and hydrogen embrittlement resistance of steel. If the Ni content is less than 0.01%, the above effects cannot be fully obtained even if the contents of other elements are within the range of this embodiment.
[0172] On the other hand, if the Ni content exceeds 0.50%, the corrosion resistance and hydrogen embrittlement resistance of the steel material will decrease.
[0173] Therefore, the Ni content is 0.01 to 0.50%.
[0174] The lower limit of the Ni content is preferably 0.05%, more preferably 0.10%, more preferably 0.15%, more preferably 0.20%, and still more preferably 0.25%.
[0175] The upper limit of the Ni content is preferably 0.45%, more preferably 0.40%.
[0176] Mo: 0.01~0.50%
[0177] Molybdenum (Mo) improves the hardenability of steel and increases the strength of fasteners made of steel. In fasteners for civil engineering and construction, the diameter sometimes exceeds 20 mm. In order to improve the strength of such thick fasteners, it is necessary to improve the hardenability of the steel used as the material. Mo is easy to improve the hardenability of steel.
[0178] On the other hand, if the Mo content exceeds 0.50%, the corrosion resistance and hydrogen embrittlement resistance of the steel material will decrease even if the contents of other elements are within the ranges of the present embodiment.
[0179] Therefore, the Mo content is 0.01 to 0.50%.
[0180] The lower limit of the Mo content is preferably 0.05%, more preferably 0.10%, further preferably 0.15%, further preferably 0.20%.
[0181] The upper limit of the Mo content is preferably 0.45%, more preferably 0.40%, and further preferably 0.35%.
[0182] Ti: 0.001~0.100%
[0183] Titanium (Ti) forms Ti nitride by bonding with N, thereby improving the strength of the fastening member made of the steel material. If the Ti content is less than 0.001%, the above-mentioned effect cannot be fully obtained.
[0184] On the other hand, if the Ti content exceeds 0.100%, even if the contents of other elements are within the range of the present embodiment, excessive Ti precipitates such as carbides and carbonitrides are generated. In this case, the corrosion resistance and hydrogen embrittlement resistance of the steel material are reduced.
[0185] Therefore, the Ti content is 0.001 to 0.100%.
[0186] The lower limit of the Ti content is preferably 0.005%, more preferably 0.010%, further preferably 0.015%, further preferably 0.018%.
[0187] The upper limit of the Ti content is preferably 0.080%, more preferably 0.060%, further preferably 0.040%, further preferably 0.030%.
[0188] One or more selected from Co, Sb, Ge and In: a total of 0.0013% or more and less than 0.0065% Cobalt (Co), antimony (Sb), germanium (Ge) and indium (In) all inhibit the dissolution of Fe in steel in an acidic environment. More specifically, these elements dissolve more preferentially than Fe in an acidic environment. After dissolution, these elements adhere to the surface of the steel in the form of oxides or metals. Therefore, the dissolution of Fe in the steel can be suppressed. As a result, the corrosion resistance and hydrogen embrittlement resistance of the steel are improved. If the total content of one or more selected from Co, Sb, Ge and In is less than 0.0013%, the above effect cannot be fully obtained.
[0189] On the other hand, if the total content of one or more selected from Co, Sb, Ge and In is 0.0065% or more, the corrosion resistance and hydrogen embrittlement resistance of the steel material are reduced.
[0190] Therefore, the total content of one or more selected from Co, Sb, Ge, and In is 0.0013% or more and less than 0.0065%.
[0191] The lower limit of the total content of one or more selected from Co, Sb, Ge, and In is preferably 0.0015%, more preferably 0.0017%, further preferably 0.0020%, further preferably 0.0022%.
[0192] The upper limit of the total content of one or more selected from Co, Sb, Ge, and In is preferably 0.0063%, more preferably 0.0061%, further preferably 0.0059%, further preferably 0.0057%.
[0193] N: 0.010% or less
[0194] Nitrogen (N) is inevitably contained, that is, the N content is greater than 0%.
[0195] N combines with Al or Ti to form nitrides or carbonitrides. These nitrides and carbonitrides suppress the coarsening of grains through the pinning effect. As a result, the cold forgeability of the steel is improved.
[0196] However, if the N content exceeds 0.010%, even if the contents of other elements are within the range of this embodiment, coarse nitrides will be generated. Coarse nitrides will become the starting point of destruction and reduce the cold forgeability of the steel. In addition, the hydrogen embrittlement resistance of the bolt will be reduced.
[0197] Therefore, the N content is set to 0.010% or less.
[0198] The lower limit of the N content is preferably 0.001%, more preferably 0.002%, and further preferably 0.003%.
[0199] The upper limit of the N content is preferably 0.009%, more preferably 0.008%, further preferably 0.007%, further preferably 0.006%.
[0200] O: 0.015% or less
[0201] Oxygen (O) is an impurity that is inevitably contained. That is, the O content is greater than 0%.
[0202] O forms oxides in the steel material. If the O content exceeds 0.015%, even if the contents of other elements are within the ranges of the present embodiment, coarse oxides reduce the hydrogen embrittlement resistance of the bolt.
[0203] Therefore, the O content is set to 0.015% or less.
[0204] The lower limit of the O content is preferably 0.001%, more preferably 0.002%, further preferably 0.003%, further preferably 0.004%.
[0205] The upper limit of the O content is preferably 0.013%, more preferably 0.011%, and further preferably 0.009%.
[0206] The remainder of the chemical composition of the steel material of this embodiment is composed of Fe and impurities. Here, the impurities in the chemical composition are substances mixed from ore, scraps or the manufacturing environment as raw materials when the steel material is manufactured industrially, and refer to substances that are allowed within the range that does not have an adverse effect on the steel material of this embodiment.
[0207] [Optional Elements]
[0208] The steel material of the present embodiment may further contain one or more elements selected from the following element group in place of a part of Fe.
[0209] W: 0~0.50%,
[0210] B: 0~0.0050%,
[0211] Nb: 0~0.300%,
[0212] Ca: 0~0.0050%,
[0213] Mg: 0 to 0.0050%, and
[0214] Rare earth elements: 0~0.0200%.
[0215] These elements are described below.
[0216] W: 0~0.50%
[0217] Tungsten (W) is an arbitrary element and may not be contained. That is, the W content may be 0%. When contained, W, like Co, Sb, Ge and In, inhibits the dissolution of Fe in the steel in a corrosive environment containing chloride ions. As a result, the corrosion resistance and hydrogen embrittlement resistance of the steel are improved. If W is contained, even in a small amount, the above-mentioned effect can be obtained to a certain extent.
[0218] However, if the W content exceeds 0.50%, the corrosion resistance and hydrogen embrittlement resistance of the steel material will be reduced even if the contents of other elements are within the ranges of the present embodiment.
[0219] Therefore, the W content is 0 to 0.50%.
[0220] The lower limit of the W content is preferably 0.01%, more preferably 0.03%, and further preferably 0.05%.
[0221] The upper limit of the W content is preferably 0.40%, more preferably 0.35%, further preferably 0.30%, further preferably 0.25%.
[0222] B: 0~0.0050%
[0223] Boron (B) is an arbitrary element and may not be contained. That is, the B content may be 0%. When contained, B improves the hardenability of the steel material and improves the strength of the fastening member formed of the steel material. In the steel material of this embodiment, the Cr content is suppressed in order to suppress the intrusion of hydrogen into the steel material in a corrosive environment. As a substitute for Cr, B improves the hardenability of the steel material together with Mo and improves the strength of the fastening member formed of the steel material. If B is contained, even in a small amount, the above-mentioned effect can be obtained to a certain extent.
[0224] However, if the B content exceeds 0.0050%, even if the contents of other elements are within the range of the present embodiment, coarse B nitrides will be generated. Coarse B nitrides will become the starting point of fracture. As a result, the cold forgeability of the steel material will be reduced.
[0225] Therefore, the B content is 0 to 0.0050%.
[0226] The lower limit of the B content is preferably 0.0001%, more preferably 0.0005%, and further preferably 0.0007%.
[0227] The upper limit of the B content is preferably 0.0045%, more preferably 0.0040%, further preferably 0.0030%, further preferably 0.0025%.
[0228] Nb: 0~0.300%
[0229] Niobium (Nb) is an arbitrary element and may not be contained. That is, the Nb content may be 0%. When contained, Nb forms Nb precipitates such as carbides and carbonitrides. Nb precipitates increase the strength of the fastening member made of steel. If the Nb content is contained, even a small amount, the above effect can be obtained to a certain extent.
[0230] However, if the Nb content exceeds 0.300%, even if the contents of other elements are within the range of this embodiment, a large amount of Nb precipitates will be generated. In this case, the amount of hydrogen intrusion into the steel material increases. As a result, the corrosion resistance and hydrogen embrittlement resistance of the steel material decrease.
[0231] Therefore, the Nb content is 0 to 0.300%.
[0232] The lower limit of the Nb content is preferably 0.001%, more preferably 0.003%, more preferably 0.005%, more preferably 0.010%, and still more preferably 0.020%.
[0233] The upper limit of the Nb content is preferably 0.250%, more preferably 0.200%, and further preferably 0.150%.
[0234] Ca: 0~0.0050%
[0235] Calcium (Ca) is an arbitrary element and may not be contained. That is, the Ca content may be 0%. When Ca is contained, that is, when Ca exceeds 0%, Ca refines MnS. Therefore, the corrosion resistance and hydrogen embrittlement resistance of the steel material are improved. If Ca is contained, even in a small amount, the above effects can be obtained to a certain extent.
[0236] However, if the Ca content exceeds 0.0050%, even if the contents of other elements are within the range of the present embodiment, coarse Ca oxides are generated. In this case, the corrosion resistance and hydrogen embrittlement resistance of the steel material are reduced.
[0237] Therefore, the Ca content is 0 to 0.0050%.
[0238] The lower limit of the Ca content is preferably 0.0001%, more preferably 0.0002%, and further preferably 0.0005%.
[0239] The upper limit of the Ca content is preferably 0.0040%, more preferably 0.0030%.
[0240] Mg: 0~0.0050%
[0241] Magnesium (Mg) is an arbitrary element and may not be contained. That is, the Mg content may be 0%. When Mg is contained, that is, when Mg exceeds 0%, Mg refines MnS. Therefore, the corrosion resistance and hydrogen embrittlement resistance of the steel material are improved. If Mg is contained, even in a small amount, the above-mentioned effect can be obtained to a certain extent.
[0242] However, if the Mg content exceeds 0.0050%, even if the contents of other elements are within the range of the present embodiment, coarse Mg oxides are generated. In this case, the corrosion resistance and hydrogen embrittlement resistance of the steel material are reduced.
[0243] Therefore, the Mg content is 0 to 0.0050%.
[0244] The lower limit of the Mg content is preferably 0.0001%, more preferably 0.0002%, and further preferably 0.0005%.
[0245] The upper limit of the Mg content is preferably 0.0040%, more preferably 0.0030%.
[0246] Rare earth elements (REM): 0~0.0200%
[0247] Rare earth elements (REM) are arbitrary elements and may not be contained. That is, the REM content may be 0%. When REM is contained, that is, when REM exceeds 0%, REM refines MnS. Therefore, the corrosion resistance and hydrogen embrittlement resistance of the steel are improved. If REM is contained, even in a small amount, the above effects can be obtained to a certain extent.
[0248] However, if the REM content exceeds 0.0200%, even if the contents of other elements are within the range of the present embodiment, coarse oxides are generated, and in this case, the corrosion resistance and hydrogen embrittlement resistance of the steel material are reduced.
[0249] Therefore, the REM content is 0 to 0.0200%.
[0250] The lower limit of the REM content is preferably 0.0001%, more preferably 0.0005%, more preferably 0.0010%, more preferably 0.0020%, and still more preferably 0.0050%.
[0251] The upper limit of the REM content is preferably 0.0150%, more preferably 0.0100%.
[0252] REM in this specification refers to one or more elements selected from scandium (Sc) with atomic number 21, yttrium (Y) with atomic number 39, and lanthanum (La) with atomic number 57 to lutetium (Lu) with atomic number 71 as lanthanoid elements. The REM content in this specification refers to the total content of these elements.
[0253] [Method for measuring the chemical composition of steel materials]
[0254] The chemical composition of the steel of the present embodiment can be determined by a known component analysis method according to JIS G0321:2017. Specifically, a drill is used to collect chips from the inside of the steel at a depth of more than 1 mm. The collected chips are dissolved in an acid to obtain a solution. The solution is subjected to ICP-AES (Inductively Coupled Plasma Atomic Emission Spectrometry) to perform elemental analysis of the chemical composition. For the C content and S content, the known high-frequency combustion method (combustion-infrared absorption method) is used to obtain. For the N content and O content, the known inert gas melting-thermal conductivity method is used to obtain.
[0255] It should be noted that the content of each element is a value obtained by rounding the decimal part of the measured value based on the significant figures specified in this embodiment to the minimum digit of the content of each element specified in this embodiment. For example, the C content of the steel material in this embodiment is specified with a value up to the second decimal place. Therefore, the C content is a value obtained by rounding the third decimal place of the measured value to the second decimal place.
[0256] The same is true for the contents of other elements other than the C content of the steel material of the present embodiment. The measured value is rounded off to the minimum number of decimal places specified in the present embodiment, and the resulting value is used as the element content.
[0257] It should be noted that rounding means: if the decimal part is less than 5, it is discarded; if the decimal part is greater than 5, it is rounded up.
[0258] [Regarding (Feature 2) Formula (1)]
[0259] The chemical composition of the steel material of the present embodiment further satisfies the formula (1) on the premise that the contents of each element are within the range of the present embodiment.
[0260] 23<10×LN(Cu+0.5×Sn+2000×Tx)+100×(0.5×Ni+Mo) 3 -100×(0.5×Ni+Mo) 2 +30×(0.5×Ni+Mo)+10<39 (1)
[0261] Here, the element symbol in formula (1) is substituted by the content of the corresponding element in mass %, and Tx is substituted by the total content of one or more selected from Co, Sb, Ge and In in mass %. LN in formula (1) refers to the natural logarithm. The natural logarithm refers to the logarithm with the natural constant e as the base.
[0262] Definition: F1 = 10 × LN (Cu + 0.5 × Sn + 2000 × Tx) + 100 × (0.5 × Ni + Mo) 3 -100×(0.5×Ni+Mo) 2 +30×(0.5×Ni+Mo)+10. F1 is an indicator of the corrosion resistance and hydrogen embrittlement resistance of steel.
[0263] Among the elements in the chemical composition that satisfies feature 1, Cu, Sn, Co, Sb, Ge, and In improve corrosion resistance in an environment containing chloride ions, while also suppressing the generation of hydrogen caused by the reduction reaction based on corrosion. If the generation of hydrogen can be suppressed, the amount of hydrogen in contact with the surface of the steel will be reduced. Therefore, the amount of hydrogen that penetrates into the steel from the surface of the steel is also reduced. As a result, the hydrogen embrittlement resistance is improved. Therefore, Cu, Sn, Co, Sb, Ge, and In can improve the corrosion resistance while suppressing the generation of hydrogen and improve the hydrogen embrittlement resistance.
[0264] In addition, among the elements in the chemical composition of feature 1, Ni and Mo improve or reduce corrosion resistance and hydrogen embrittlement resistance according to their contents through the synergistic effect with Sn in the chemical composition satisfying feature 1. Specifically, in the chemical composition satisfying feature 1, although the corrosion resistance and hydrogen embrittlement resistance are improved when the content of Ni and Mo is within a certain range, the corrosion resistance and hydrogen embrittlement resistance are reduced in different ranges. It can be considered that the synergistic effect of Ni and Mo with Sn affects the level of corrosion resistance and hydrogen embrittlement resistance based on Ni and Mo.
[0265] "100×(0.5×Ni+Mo)" in F1 3 -100×(0.5×Ni+Mo) 2 +30×(0.5×Ni+Mo)+10” is a cubic formula. This cubic formula represents the relationship between the contents of Ni and Mo and the corrosion resistance and hydrogen embrittlement resistance in the chemical composition of feature 1 containing Sn.
[0266] When F1 is higher than 23 and lower than 39, the relationship between the contents of Cu, Sn, Co, Sb, Ge and In and the contents of Ni and Mo is appropriate in the chemical composition satisfying feature 1. Therefore, in a corrosive environment containing chloride ions, both excellent corrosion resistance and excellent hydrogen embrittlement resistance can be achieved.
[0267] Therefore, F1 is higher than 23 and lower than 39.
[0268] The preferred lower limit of F1 is 24, more preferably 25, and even more preferably 26.
[0269] The upper limit of F1 is preferably 38, more preferably 36, and even more preferably 34.
[0270] The F1 value is an integer. That is, the F1 value is a value obtained by rounding off the first decimal place of the obtained value.
[0271] [About the Microstructure of the Steel Material of the Present Embodiment]
[0272] The microstructure of the steel material of the present embodiment is not particularly limited. When the steel material of the present embodiment is used as a fastening member, if the hardness of the steel material is too high, annealing treatment may be performed. The cold forging property of the steel material after annealing is improved. Therefore, the steel material of the present embodiment can be used as a material and cold forging can be performed to manufacture a fastening member. Therefore, the microstructure of the steel material of the present embodiment is not particularly limited.
[0273] For example, when the diameter of the steel material is set to D, in the cross section perpendicular to the longitudinal direction of the steel material, in the microstructure at a depth position of D / 4 in the radial direction from the surface of the steel material, the area ratio of pearlite is 10% or less, and the portion other than the pearlite includes one or more selected from polygonal ferrite, bainitic ferrite, acicular ferrite, and martensite. It should be noted that in this specification, pearlite includes pseudo-pearlite. Figure 1 An example of a photographic image of the microstructure at a depth position D / 4 of the steel material according to the present embodiment is shown in FIG. Figure 1 The portion with low brightness in the steel is pearlite, and the portion other than the pearlite includes one or more selected from polygonal ferrite, bainitic ferrite, acicular ferrite, and martensite. However, the microstructure of the steel material of this embodiment is not limited to the above-mentioned microstructure.
[0274] [Microstructure observation method]
[0275] The microstructure of steel can be observed by the following methods.
[0276] In the cross section of the steel material perpendicular to the long side direction, the surface including the radial depth position D / 4 from the surface of the steel material is defined as the observation surface. Here, as mentioned above, D refers to the diameter of the steel material. Collect a sample including the observation surface. Mirror-polish the observation surface of the sample. Etch the mirror-polished observation surface with 3% nitric acid (nitric acid etching solution). Observe any observation field (0.5mm×0.5mm) in the etched observation surface with a 500x optical microscope. Determine each structure in the observation field and calculate the area ratio (%).
[0277] [Application of the steel material according to the present embodiment]
[0278] The steel material of this embodiment can be used as a material for fastening members of industrial machinery, automobiles, bridges, buildings, etc. Here, the fastening member includes a bolt, a nut, and a washer. The shape of the steel material of this embodiment is not particularly limited. The shape of the steel material can be a bar steel or a wire rod, or a steel plate.
[0279] [Method for manufacturing steel materials]
[0280] An example of a method for manufacturing the steel material of the present embodiment is described. The method for manufacturing the steel material described below is an example for manufacturing the steel material of the present embodiment. Therefore, the steel material having the above-mentioned structure can also be manufactured by other manufacturing methods other than the manufacturing method described below. However, the manufacturing method described below is a preferred example of the method for manufacturing the steel material of the present embodiment.
[0281] An example of the method for producing the steel material according to the present embodiment includes the following steps.
[0282] (Process 1) Process of preparing materials (material preparation process)
[0283] (Step 2) Step of manufacturing steel by hot working the material (hot working step)
[0284] Hereinafter, each step will be described.
[0285] [(Process 1) Material preparation process]
[0286] In the material preparation process, the material of the steel material of the present embodiment is prepared. Specifically, molten steel having a content of each element in the chemical composition within the range of the present embodiment is manufactured. The refining method is not particularly limited, as long as a known method is used. For example, the molten iron manufactured by a known method is subjected to refining in a converter (primary refining). The molten steel tapped from the converter is subjected to a known secondary refining. In the secondary refining, the content of the alloying elements in the molten steel is adjusted to manufacture a molten steel having a chemical composition with a content of each element within the range of the present embodiment.
[0287] The molten steel produced by the above-mentioned refining method is used to produce a material by a known casting method. For example, a steel ingot can be produced by an ingot casting method using the molten steel. Alternatively, a steel block or a steel billet can be produced by a continuous casting method using the molten steel. The material (steel ingot, steel block or steel billet) is produced by the above method.
[0288] [(Process 2) Hot working process]
[0289] In the hot working step, the material (steel ingot, steel block or steel billet) prepared in the material preparation step is hot worked to manufacture the steel material of the present embodiment. The shape of the steel material is not particularly limited, and it may be, for example, a steel bar or a wire. In the following description, as an example, the case where the steel material is a steel bar or a wire is described. However, even if the steel material is a steel plate, it can be manufactured by the same hot working step.
[0290] The hot working process includes the following steps. The main conditions in each step are as follows.
[0291] (Process 21) Billet rolling process
[0292] (Process 22) Finishing process
[0293] (Process 23) Cooling process
[0294] Hereinafter, each step will be described.
[0295] [(Process 21) slab rolling process]
[0296] In the bloom rolling process, the material is hot rolled to produce a steel bloom.
[0297] Specifically, in the flaking rolling process, the material is subjected to hot rolling (flaking rolling) by a flaking rolling mill to produce a steel billet. When a continuous rolling mill is arranged downstream of the flaking rolling mill, the steel billet after flaking rolling can be further subjected to hot rolling by the continuous rolling mill to further produce a steel billet of a smaller size. In the continuous rolling mill, a horizontal frame having a pair of horizontal rollers and a vertical frame having a pair of vertical rollers are alternately arranged in a row. As described above, in the flaking rolling process, the material is produced into a steel billet using a flaking rolling mill, or using a flaking rolling mill and a continuous rolling mill.
[0298] The heating temperature in the bloom rolling process may be in a known temperature range, and the heating temperature is, for example, 1100 to 1300° C. The steel slab produced by the bloom rolling process is naturally cooled (air-cooled) to room temperature before the finish rolling process.
[0299] [(Process 22) Finishing rolling process]
[0300] In the finish rolling process, first, a steel slab cooled to room temperature is heated using a heating furnace, and then hot-rolled using a continuous rolling mill to produce a steel bar or wire rod as a steel material.
[0301] The heating temperature in the heating furnace in the finishing process may be within a known range. The heating temperature may be, for example, 900 to 1050°C. In the finishing process, hot rolling (finishing rolling) is performed by a continuous rolling mill having a plurality of rolling stands arranged in a row. In hot rolling using a continuous rolling mill, the temperature of the steel at the exit side of the stand that finally presses down the steel is defined as the finishing temperature (°C). The finishing temperature may be within a known range. The finishing temperature may be, for example, 800°C or more and less than 900°C.
[0302] [(Step 23) Cooling Step]
[0303] In the cooling process, the steel material after the finishing rolling process is cooled. Here, the arithmetic mean (°C / second) of the cooling rate at the finishing rolling temperature FT to 300°C is defined as the average cooling rate. The average cooling rate may be within a known range. The average cooling rate CR1 is, for example, 0.6 to 1.8°C / second.
[0304] It should be noted that in the hot working process of the above-mentioned manufacturing process, the slab rolling process may not be performed but the finishing rolling process may be performed. That is, the slab rolling process is an arbitrary process. For example, when a steel slab is prepared in the material preparation process, the slab rolling process may be omitted and the finishing rolling process may be performed.
[0305] [About the fastening member of the present embodiment]
[0306] The fastening member of the present embodiment is made of the steel material of the present embodiment described above. That is, the fastening member of the present embodiment satisfies the features 1 and 2. As described above, the fastening member is, for example, a bolt, a nut, and a washer.
[0307] [Method for manufacturing a fastening member made of the steel material of this embodiment]
[0308] The method for manufacturing the fastening member made of the steel material of the present embodiment is a well-known manufacturing method. The method for manufacturing the fastening member includes the following steps, for example.
[0309] (Process 31) Wire drawing process
[0310] (Process 32) Cold Forging Process
[0311] (Process 33) Quenching and tempering process
[0312] Hereinafter, each step will be described.
[0313] [(Process 31) Wire drawing process]
[0314] In the wire drawing process, the steel material is subjected to a known wire drawing process to produce a steel wire. The wire drawing process may be performed only once or multiple times such as twice.
[0315] [(Process 32) Cold forging process]
[0316] In the cold forging step, the steel wire after the wire drawing step is subjected to known cold forging to produce an intermediate product having the shape of a fastening member.
[0317] [(Process 33) Quenching and tempering process]
[0318] In the quenching and tempering process, the intermediate product is quenched and tempered.
[0319] [Quenching]
[0320] Quenching can be implemented by a known method. The quenching temperature and the holding time at the quenching temperature can be in a known range. The quenching temperature is, for example, 840 to 970°C. The holding time at the quenching temperature is, for example, 15 minutes to 360 minutes (6 hours). The intermediate product after the holding time is quenched. Specifically, the intermediate product is water-cooled or oil-cooled.
[0321] [Tempering]
[0322] The intermediate product after quenching is tempered. The tempering temperature and the holding time at the tempering temperature may be in a known range. The tempering temperature is, for example, 400 to 550° C. The holding time at the tempering temperature is 0.5 to 6.0 hours.
[0323] The above-described manufacturing method can manufacture a fastening member made of the steel material of the present embodiment. The manufactured fastening member can obtain sufficient corrosion resistance and sufficient hydrogen embrittlement resistance in a corrosive environment containing chloride ions.
[0324] Example
[0325] The effects of the steel material of this embodiment will be further specifically described by way of examples. The conditions in the following examples are one condition example adopted to confirm the feasibility and effects of the steel material of this embodiment. Therefore, the steel material of this embodiment is not limited to this one condition example.
[0326] [Material preparation process]
[0327] Molten steel having the chemical compositions shown in Table 1-1 and Table 1-2 was produced. A material (cast slab) was produced by continuous casting using the molten steel.
[0328] [Table 1-1]Table 1-1
[0329]
[0330] [Table 1-2]
[0331] Table 1-2
[0332]
[0333] [Hot working process]
[0334] The manufactured material is subjected to a bloom rolling process to manufacture a steel slab. In the bloom rolling process, the material is heated to 1100 to 1300° C., and then hot rolled using a bloom rolling mill and a continuous rolling mill. The steel slab manufactured by the bloom rolling process is naturally cooled to room temperature.
[0335] The manufactured steel billet was subjected to a finishing rolling process. In the finishing rolling process, the steel billet was heated at 900 to 1050°C. The heated steel billet was hot rolled using a continuous rolling mill to produce a steel material (steel bar) with a diameter of 22 mm. The finishing rolling temperature in the hot rolling is above 800°C and below 900°C. The hot-rolled steel material (steel bar) is cooled. At this time, the average cooling rate from the finishing rolling temperature to 300°C is 0.6 to 1.8°C / second.
[0336] [Table 2]
[0337] surface
[0338]
[0339] Through the above-mentioned manufacturing process, steel materials of respective test numbers were manufactured.
[0340] [About evaluation test]
[0341] The following steel material evaluation tests (Test 1 to Test 4) were performed on the manufactured steel materials of each test number.
[0342] (Test 1) Chemical composition test of steel
[0343] (Test 2) Hot workability evaluation test
[0344] (Test 3) Corrosion resistance evaluation test
[0345] (Test 4) Hydrogen embrittlement resistance evaluation test
[0346] Hereinafter, each test will be described.
[0347] [(Test 1) Chemical composition measurement test of steel materials]
[0348] The chemical composition of the steel material (steel bar) of each test number was analyzed based on the above-mentioned [Method for measuring the chemical composition of steel material]. As a result, the chemical composition of each test number is as shown in Table 1-1 and Table 1-2.
[0349] [(Test 2) Hot workability evaluation test]
[0350] For the steel material (steel bar) of each test number, it was confirmed whether cracks were generated during the hot working process. If cracks were generated during the hot working, it was judged that the hot workability was low (recorded as "B" (Bad) in the "Hot Workability" column in Table 2). On the other hand, if cracks were not generated in the steel material during the hot working process, it was judged that the hot workability was excellent (recorded as "E" (Excellent) in the "Hot Workability" column in Table 2).
[0351] [(Test 3) Corrosion resistance evaluation test]
[0352] The corrosion resistance of the steel material of each test number was evaluated by the following test.
[0353] In the corrosion resistance evaluation test, considering the ease of corrosion resistance evaluation, steel bars were not used as materials, and steel plates of each test number were manufactured by the following method instead of steel bars. Specifically, the materials having the chemical compositions of Tables 1-1 and 1-2 were subjected to a finishing rolling process and a cooling process to manufacture steel plates of each test number with a plate thickness of 6 mm. The temperature of the steel plate at the start of finishing rolling was 900 to 1050°C. The finishing rolling temperature was above 800°C and below 900°C. The average cooling rate from the finishing rolling temperature to 300°C was 0.6 to 1.8°C / second.
[0354] The steel plate was subjected to quenching and tempering to simulate the manufacturing process of the bolt. Quenching was carried out using a heat treatment furnace. The quenching temperature was set to 880°C, and the holding time at the quenching temperature was set to 60 minutes. After the holding time, the steel plate was immersed in oil at 60°C and quenched. It should be noted that the heat treatment furnace was set to a gas atmosphere filled with Ar gas to suppress decarburization of the steel plate. Tempering was carried out after quenching. Tempering was carried out using a heat treatment furnace. The tempering temperature was set to 450°C, and the holding time at the tempering temperature was set to 90 minutes.
[0355] A plate-shaped test piece of 100 mm×60 mm×3 mm thick was collected from the steel plate after quenching and tempering. The surface of the collected plate-shaped test piece was shot peened, and the surface of the plate-shaped test piece was adjusted to a ten-point average roughness Rzjis of 75 μm in accordance with JIS B0601:2001.
[0356] The surface of the plate test piece after shot blasting was painted to form a coating film consisting of a primer layer with a thickness of 120 μm (manufactured by Shinto Paint Co., Ltd., trade name: Neogose #2300PS), a middle coating layer with a thickness of 30 μm (manufactured by Shinto Paint Co., Ltd., trade name: Shintofreon #100), and an outer coating layer with a thickness of 25 μm (manufactured by Shinto Paint Co., Ltd., trade name: Shintofreon #100).
[0357] The coating film defects reaching the blank (steel sheet) were formed using a cutter, and the total length of the coating film defects was set to 500 mm.
[0358] A corrosion test in accordance with the US standard SAE J2334 was performed using a plate-shaped test piece having coating film defects using a dry-wet repetitive tester capable of salt water immersion. Specifically, a test was performed in which the following three steps (total 24 hours) constituted one cycle.
[0359] (Step 1: Wetting process)
[0360] The plate-shaped test piece was kept in an environment of 50° C. and 100% RH for 6 hours.
[0361] (Step 2: Salt water immersion process)
[0362] The plate-shaped test piece after step 1 was immersed in an aqueous solution of pH 8 containing 0.5% NaCl, 0.1% CaCl 2 and 0.075% NaHCO 3 for 15 minutes.
[0363] (Step 3: Drying process)
[0364] The plate-shaped test piece after step 2 was kept in an environment of 60° C. and 50% RH for 17.75 hours, and the plate-shaped test piece after keeping was dried.
[0365] The above steps 1 to 3 constituted one cycle, and 80 cycles were performed.
[0366] In the coating of the plate-shaped test piece after 80 cycles, the coating portion (hereinafter referred to as the coating peeling portion) that peeled off from the surface of the test piece starting from the coating defect was removed by a cutter. After removing the coating peeling portion, an image of the coating of the plate-shaped test piece viewed from above was generated. By image processing, the area where the coating remained on the surface of the plate-shaped test piece and the area where the steel plate was exposed (coating peeling portion) were distinguished. Then, the total area of the coating peeling portion (peeling area) was calculated. Based on the total area of the coating peeling portion and the area of the surface of the plate-shaped test piece where the coating was formed, the peeling area rate (%) of the coating was calculated. The peeling area rate calculated is shown in the "Peeling Area Rate (%)" column of Table 2.
[0367] [(Test 4) Hydrogen embrittlement resistance evaluation test]
[0368] The hydrogen embrittlement resistance of the steel material of each test number was evaluated by the following test.
[0369] First, the steel (steel bar) was subjected to quenching and tempering to simulate the manufacturing process of the bolt. Quenching was carried out using a heat treatment furnace. The quenching temperature was set to 880°C, and the holding time at the quenching temperature was set to 60 minutes. The steel after the holding time was immersed in oil at 60°C and oil quenched. It should be noted that the heat treatment furnace was set to a gas atmosphere filled with Ar gas to suppress the decarburization of the steel. Tempering was carried out after quenching. Tempering was carried out using a heat treatment furnace. The tempering temperature was set to 450°C, and the holding time at the tempering temperature was set to 90 minutes.
[0370] The amount of hydrogen intrusion into the steel material of each test number after the above quenching and tempering treatment was measured by the following method (hydrogen intrusion amount investigation test).
[0371] First, a test piece was collected from the center of the cross section perpendicular to the axial direction of the steel material (steel bar). The test piece was made into a round bar test piece with a diameter of 7 mm and a length of 100 mm. The central axis of the test piece was coaxial with the steel material. Two test pieces were prepared for each test number.
[0372] A corrosion test was performed in accordance with the US standard SAE J2334, and the amount of hydrogen intrusion into each test piece after the corrosion test was measured.
[0373] Specifically, the amount of hydrogen intrusion was measured for the test pieces after 56 cycles of test, taking steps 1 to 3 of test 3 as one cycle. Before measuring the amount of hydrogen intrusion, the test pieces after the corrosion test were immersed in liquid nitrogen so that the hydrogen intruded into the test pieces after the corrosion test would not escape. Before measuring the amount of hydrogen intrusion, the corrosion products attached to the surface of the test pieces were completely removed by sandblasting. The amount of hydrogen intrusion was measured for the test pieces from which the corrosion products were removed using a temperature-rising detachment analyzer. Specifically, the amount of diffusible hydrogen detected by the detachment reaction from room temperature to 200°C was measured using a temperature-rising detachment analyzer as the amount of hydrogen intrusion. The arithmetic mean of the amount of hydrogen intrusion of the two test pieces obtained is defined as the amount of hydrogen intrusion He (ppm) of the steel of the test number.
[0374] Next, a hydrogen embrittlement resistance evaluation test was performed by the following method.
[0375] The test piece was collected from the center of the cross section perpendicular to the axial direction of the above-mentioned quenched and tempered steel (steel bar). The test piece was made into a round rod test piece with a diameter of 7mm and a length of 70mm and an annular cut. An annular cut was formed in the center of the long side direction of the test piece. The depth of the cut was 1.4mm, the angle of the cut was 60°, and the curvature radius of the cut bottom was 0.175mm.
[0376] The SSRT (Slow Strain Rate Technique) test was performed using a prepared round bar test piece with an annular cut. Specifically, a hydrogenation solution was prepared by adding 3g / L of NH4SCN to a 3% NaCl solution. While the round bar test piece with an annular cut was immersed in the hydrogenation solution, the current density applied to the test piece was adjusted to adjust the amount of hydrogen intrusion into the test piece.
[0377] The round bar test piece with an annular cut that was hydrogenated at each current density was plated so that hydrogen would not escape. The round bar test piece with an annular cut after the plating treatment was placed at room temperature for more than 8 hours. Then, a tensile test was performed at a speed of 0.005 mm / min to break the round bar test piece with an annular cut. After the break, the amount of hydrogen intrusion (ppm) of the round bar test piece with an annular cut was measured using a temperature rise separation analysis device.
[0378] Through the above experiments, the Figure 2 The graph of the hydrogen intrusion amount (ppm) and the breaking load (kN) is shown as an example. Based on the graph, the breaking load (σ) at a hydrogen amount (2He) that is twice the hydrogen intrusion amount (He) obtained in the hydrogen intrusion amount investigation test was calculated. 2He ).
[0379] Furthermore, a tensile test was performed on the circular notch round bar test piece of each test number which was not filled with hydrogen at a speed of 0.005 mm / min, and the circular notch round bar test piece was broken to determine the breaking load (σ0).
[0380] The breaking load σ when hydrogen is charged 2He Divided by the breaking load when not charged with hydrogen (σ0), the breaking load ratio (σ 2He / σ0).
[0381] Based on the breaking load ratio (σ 2He / σ0) was used to evaluate hydrogen embrittlement resistance. The evaluation results are shown in the "Hydrogen embrittlement resistance" column in Table 2. If the fracture load ratio is 0.8 or more, it is judged that the hydrogen embrittlement resistance is excellent (indicated by "E" in Table 2). If the fracture load ratio is less than 0.8, it is judged that the hydrogen embrittlement resistance is low (indicated by "B" in Table 2).
[0382] [Evaluation results]
[0383] Table 2 shows the evaluation results.
[0384] In test numbers 1 to 26, the chemical composition is appropriate, and F1 satisfies formula (1). Therefore, the peeling area ratio is 40% or less, and sufficient corrosion resistance is obtained. In addition, sufficient hydrogen embrittlement resistance is obtained. It should be noted that the microstructures of these test numbers are all: the pearlite area ratio is 10% or less, and the part other than the pearlite contains one or more structures selected from polygonal ferrite, bainitic ferrite, acicular ferrite, and martensite. Therefore, the hot workability of these test numbers is excellent.
[0385] On the other hand, in Test No. 27, the Sn content was low. Therefore, the peeling area ratio exceeded 40%, and the corrosion resistance was low. In addition, sufficient hydrogen embrittlement resistance could not be obtained.
[0386] In Test No. 28, the Sn content was high and therefore the hot workability was low.
[0387] In Test No. 29, the Cr content was too high. Therefore, the peeling area ratio exceeded 40%, and the corrosion resistance was low. In addition, sufficient hydrogen embrittlement resistance could not be obtained.
[0388] In test number 30, the Cu content was too low. Therefore, the peeling area ratio exceeded 40%, and the corrosion resistance was low. In addition, sufficient hydrogen embrittlement resistance could not be obtained.
[0389] In Test No. 31, the Cu content was too high. Therefore, the peeling area ratio exceeded 40%, and the corrosion resistance was low. In addition, sufficient hydrogen embrittlement resistance could not be obtained.
[0390] In test number 32, the total content Tx of Co, Sb, Ge, and In was too high. The peeling area ratio exceeded 40%, and the corrosion resistance was low. In addition, sufficient hydrogen embrittlement resistance could not be obtained.
[0391] In test numbers 33 and 34, the total content Tx of Co, Sb, Ge, and In was too low. Therefore, the peeling area ratio exceeded 40%, and the corrosion resistance was low. In addition, sufficient hydrogen embrittlement resistance could not be obtained.
[0392] In test number 35, the Ni content was too high. Therefore, the peeling area ratio exceeded 40%, and the corrosion resistance was low. In addition, sufficient hydrogen embrittlement resistance could not be obtained.
[0393] In test number 36, the Mo content was too high. Therefore, the peeling area ratio exceeded 40%, and the corrosion resistance was low. In addition, the hydrogen embrittlement resistance was also reduced.
[0394] In test number 37, the W content was too high. Therefore, the peeling area ratio exceeded 40%, and the corrosion resistance was low. In addition, the hydrogen embrittlement resistance was also reduced.
[0395] In test numbers 38 and 39, F1 exceeded the upper limit of formula (1). Therefore, the peeling area ratio exceeded 40%, and the corrosion resistance was low. In addition, the hydrogen embrittlement resistance was also reduced.
[0396] In test numbers 40 and 41, F1 was lower than the lower limit of formula (1). Therefore, the peeling area ratio exceeded 40%, and the corrosion resistance was low.
[0397] The embodiments of the present disclosure have been described above. However, the above embodiments are merely examples for implementing the present disclosure. Therefore, the present disclosure is not limited to the above embodiments, and the above embodiments can be appropriately modified and implemented without departing from the gist thereof.
Claims
1. A steel material comprising, by mass %, C:0.15~0.45%、 Si: 0.01-1.00%, Mn: 0.01~1.50%, P: 0.050% or less, S: 0.050% or less, Al: 0.100% or less, Sn: 0.02~0.30%, Cr: 0.20% or less, Cu: 0.010~0.500%, Ni: 0.01~0.50%, Mo: 0.01~0.50%, Ti: 0.001~0.100%, One or more selected from Co, Sb, Ge and In: 0.0013% or more and less than 0.0065% in total, N: 0.010% or less, O: 0.015% or less, W:0~0.50%、 B:0~0.0050%、 Nb: 0~0.300%, Ca: 0~0.0050%, Mg: 0~0.0050%, Rare earth elements: 0 to 0.0200%, and Balance: Fe and impurities, The steel material satisfies formula (1): 23.10×LN(Cu+0.5×Sn+2000×Tx)+100×(0.5×Ni+Mo). 3 100 × (0.5 × Ni+Mo) 2 +30×(0.5×Ni+Mo)+10×39 (1) In the formula, the element symbol in formula (1) is substituted by the content of the corresponding element in mass %, Tx is substituted by the total content of one or more selected from Co, Sb, Ge and In in mass %, and LN in formula (1) refers to the natural logarithm.
2. The steel material according to claim 1, comprising one or more selected from the following: W:0.01~0.50%、 B:0.0001~0.0050%、 Nb: 0.001~0.300%, Ca: 0.0001~0.0050%, Mg: 0.0001 to 0.0050%, and Rare earth elements: 0.0001~0.0200%.
3. A fastening member, comprising the steel material according to claim 1 or 2.
Citation Information
Patent Citations
Steel for bolt
JP2017226878A
Steel material for bolt
JP2020180325A
Cited By
Corrosion-resistant hot galvanizing foundation bolt and preparation method thereof
CN119824327A
A corrosion-resistant hot-dip galvanized anchor bolt and its preparation method
CN119824327B